IMPROVEMENT OF NON SPECIFIC IMMUNE SYSTEM ON COMMON CARP (Cyprinus carpio) AGAINST KOI HERPESVIRUS DISEASE (KHVD) BY ADDITION OF ASCORBIC ACID ON FISH DIET: A FIELD SCALE STUDY - Taukhid Taukhid; Desy Sugiani; Angela Mariana Lusiastuti (Indonesian Aquaculture Journal, 2010)
The research with the aim to know the optimal feeding frequency of supplemented ascorbic acid (microencapsulated vitamin C CFC-90) on the dose of 750 mg/kg feed to control Koi Herpesvirus (KHV) disease infecting common carp has been done in field condition. Fish were reared in floating cages with the size of 3.5 m x 3.5 m x 2.0 m and stocking density of 1,250 fish/cage with the size range of ± 10 g/fish. The treatments applied in the research were: (A) daily application, (B) every 3 days application, and (C) without vitamin C addition as the control. Fish test were challenged to KHV infection on the mid cultivation by cohabitation method in the laboratory scale for 2 weeks. Examination on behavior, clinical sign, and mortality of fish test conducted daily. The results showed that the highest survival rate was found on the application of vitamin C every 3 days (60.16%); and followed by every day (52.00%), and the lowest was found on the control group (47.36%).